GERMINATED BLACK RICE (GEMAR) FUNCTIONAL BEVERAGE POWDER: A POTENTIAL ANTIOXIDANT FOR MANAGING DIABETES MELLITUS - Sudana Fatahillah Pasaribu; Putra Chandra; Reno Irwanto; Nisya Ayu Rachmawati; Ratna Sari Dinaryanti (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background Diabetes mellitus (DM) is a degenerative disease and a leading global cause of death, often linked to increased oxidative stress and free radicals. Prolonged DM can lead to various complications, including kidney issues, heart problems, vision impairment, and more. Dietary regulation is a recommended approach to managing DM. GEMAR beverage powder, derived from germinated black rice and mung bean, holds the potential as a source of antioxidants and is beneficial for individuals with DM due to its rich phytochemical content. Objective This study aims to determine the yield and antioxidant activity of GEMAR powder beverage as a therapy for DM. Methods This is a quantitative research study employing a true experimental design, which will be analyzed descriptively. The ingredients GEMAR beverage powder germinated black rice, germinated mung bean, tempeh, red spinach, skimmed milk, soy protein isolate, and maltodextrin. The GEMAR beverage powder production includes sorting, mixing, roasting, drying, milling, and filtration stages. The GEMAR beverage yield value was obtained by comparing the final powder weight and the initial powder weight. Analysis of the antioxidant activity of GEMAR beverage powder using the DPPH method. Results The yield of GEMAR beverage powder was 41,6% and the antioxidant activity of GEMAR powder beverage was 24,30±0,07%. Conclusion This study concluded that GEMAR beverage powder is a functional beverage that has antioxidant activity and has the potential to be used as a therapy for DM. Keywords: antioxidants; functional beverages; black rice; diabetes mellitus.